Analysis Of Risk Factors For Diarrhea In Toddlers In The Mulyorejo Community Health Center Working Area - Salsabilla; Yulia Khairina Ashar (Universitas Muhammadiyah Palu, 2026)
Background: Diarrhea is still the leading cause of morbidity and mortality in children under five, with millions of cases each year globally and thousands of cases in Indonesia. Objective: This study aims to analyze factors related to the incidence of diarrhea in toddlers in the work area of the Mulyorejo Health Center. Methods: The study used a quantitative approach with a cross sectional study design. The sample consisted of 105 mothers who had toddlers, selected using stratified random sampling techniques. Data were collected through questionnaires and analyzed univariate and bivariate using Chi-Square tests, as well as multivariate. Results: The results showed that there was a significant relationship between the incidence of diarrhea and parental income (p = 0.114), history of breastfeeding (p = 0.024), mother's hand washing (p = 0.044), nutritional status of toddlers (p = 0.017), clean water sources (p = 0.026), family toilet conditions (p = 0.044), and garbage disposal (p = 0.019). On the other hand, there was no significant relationship between the incidence of diarrhea and maternal education level, age of toddlers, and wastewater disposal (p > 0.05). Multivariate analysis showed that the nutritional status of toddlers was the most influential factor in the incidence of diarrhea (p = 0.009). Conclusion: Environmental sanitation factors and socioeconomic conditions, especially parental income, significantly affect the incidence of diarrhea in toddlers. Interventions to improve sanitation and family economic empowerment need to be a priority in efforts to prevent diarrhea.